Dispelling Dampness, Relieving Turbidity and Dredging Collaterals Decoction, Attenuates Potassium Oxonate-Induced Hyperuricemia in Rat Models - Liu HB; Yang M; Li W; Luo T; Wu Y; Huang XY; Zhang YL; Liu T; Luo Y (Dove Medical Press, 2023)
Hai-bo Liu,1,* Min Yang,2,* Wan Li,2 Ting Luo,2 Yang Wu,2 Xiang-yu Huang,2 Yao-lei Zhang,3 Tao Liu,2 Yong Luo2,* 1Department of Biomedical Engineer, General Hospital of Western Theater Command, Chengdu, Sichuan, People's Republic of China; 2Department of Traditional Chinese Medicine, General Hospital of Western Theater Command, Chengdu, Sichuan, People's Republic of China; 3Basic Medical Laboratory, General Hospital of Western Theater Command, Chengdu, Sichuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Yong Luo, Department of Traditional Chinese Medicine, General Hospital of Western Theater Command, Chengdu, Sichuan, 610083, People's Republic of China, Tel +86 28-86571619, Email yongl019@sina.comPurpose: Dispelling dampness, relieving turbidity and dredging collaterals decoction (DED), is a traditional Chinese medicine used in the treatment of hyperuricemia. We aimed to explore the effect and mechanism of DED in the treatment of hyperuricemia.Methods: The effects of DED (9.48, 4.74, and 2.37 g/kg/d) on potassium oxonate (750 mg/kg/d)-induced hyperuricemia in rats were evaluated by serum uric acid (UA), creatinine (CRE), blood urea nitrogen (BUN), and renal pathological changes. Network pharmacology was used to identify the effective components and targets of DED, and the key targets and signaling pathways for its effects on hyperuricemia were screened. Molecular docking was used to predict the action of DED. H&E, immunohistochemistry, WB, and PCR were used to validate the network pharmacology results.Results: DED can effectively alleviate hyperuricemia, inhibit UA, CRE, BUN, and xanthine oxidase (XOD) activity, and reduce renal inflammatory cell infiltration and glomerular atrophy. The experiment identified 27 potential targets of DED for hyperuricemia, involving 9 components: wogonin, stigmasterol 3-O-beta-D-glucopyranoside, 3β-acetoxyatractylone, beta-sitosterol, stigmasterol, diosgenin, naringenin, astilbin, and quercetin. DED can relieve hyperuricemia mainly by inhibiting RAGE, HMGB1, IL17R, and phospho-TAK1, and by regulating the AGE-RAGE and IL-17 signaling pathways.Conclusion: DED can alleviate hyperuricemia by inhibiting XOD activity and suppressing renal cell apoptosis and inflammation via the AGE-RAGE signaling pathway and IL-17 signaling pathway. This study provides a theoretical basis for the clinical application of DED.Graphical Abstract: Keywords: dispelling dampness, relieving turbidity, dredging collaterals, hyperuricemia, network pharmacology